Identificación de bacterias endófitas asociadas a raíces de Cattleya quadricolor Lindl. - Guerrero, Luz Ángela; Pérez Quiroga, Jissel; Quintero, María Alejandra; Rojas Triviño, Alberto; Tupac Otero, J. (Lankesteriana: International Journal on Orchidology, 2013)
.